Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Citra Perusahaan - Ramadhita, Sandy; Halilah, Ii (POLITEKNIK NEGERI BANDUNG, 2015)
Companies that carry out social responsibility consistently will get broad support from the community to benefit from the various activities performed. CSR will enhance the company's image and for a long period, it will be accumulated into company's reputation. However, in order to enhance the corporate image, CSR requires a good planning. This study aims to determine the effect of CSR Desa Mandiri Energi on the image of PT PLN (Persero) Distribusi Jawa Barat dan Banten. The object of this study is the occupant Boarding Sindangsari, Cijerah, Melong, Cimahi City. This study uses two variables, namely CSR (X) and Image (Y). The method used is the quantitative method. Data collected through questionnaires to 100 respondents. The analysis in this research is conducted through validity test, reliability test, Pearson correlation analysis, coefficient determination test, simple linear regression analysis, and t test using SPSS 22. The benefit of this study is to provide information about CSR programs that have a positive influence on the image of the company and can be used as references to complete further studies. The conclusion from this research is known that CSR has a relationship to the image of 0.718. CSR influenced significantly by 0.516, or by 51.6% against the image of PT PLN (Persero) Distribusi Jawa Barat dan Banten.